2016
DOI: 10.1353/aad.2016.0000
|View full text |Cite
|
Sign up to set email alerts
|

College and Career Readiness: Course Taking Of Deaf and Hard of Hearing Secondary School Students

Abstract: Research shows that deaf and hard of hearing (DHH) students frequently enter college and the workplace relatively unprepared for success in math, science, and reading. Based on data from the National Longitudinal Transition Study-2 (NLTS2), the present study focused on DHH students' college and career readiness by investigating their opportunities in secondary school to acquire college and career skills. DHH students earned more credits overall than hearing peers; both groups earned a similar number of credits… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 40 publications
0
16
0
1
Order By: Relevance
“…From the early school years through postsecondary education, they experience various barriers to learning created by educational settings that all too often assume, erroneously, that they learn just like their hearing peers (Kral, Kronenberger, Pisoni, & O’Donoghue, 2016; Marschark & Knoors 2012). Not unrelated to these factors, deaf learners historically have demonstrated chronic underachievement from the school years through college (e.g., Cuculick & Kelly, 2003; Nagle, Shaver, Newman, & Marschark, 2016; Qi & Mitchell, 2012), despite parents’, teachers’, and researchers’ efforts to close the gap between them and their hearing peers.…”
mentioning
confidence: 99%
“…From the early school years through postsecondary education, they experience various barriers to learning created by educational settings that all too often assume, erroneously, that they learn just like their hearing peers (Kral, Kronenberger, Pisoni, & O’Donoghue, 2016; Marschark & Knoors 2012). Not unrelated to these factors, deaf learners historically have demonstrated chronic underachievement from the school years through college (e.g., Cuculick & Kelly, 2003; Nagle, Shaver, Newman, & Marschark, 2016; Qi & Mitchell, 2012), despite parents’, teachers’, and researchers’ efforts to close the gap between them and their hearing peers.…”
mentioning
confidence: 99%
“…Findings from the first causal comparative study indicated students who were deaf and hard of hearing (DHH) who attended special secondary schools were more likely to use sign language and have (a) higher hearing loss levels, (b) lower functional scores, and (c) difficulty communicating with others compared with DHH students who attended public high schools (Shaver, Marschark, Newman, & Marder, 2014). Results from the second causal comparative study found students who were DHH earned (a) more credits overall than hearing peers; (b) more vocational and nonacademic courses; (c) fewer credits in science, social studies, and foreign language; (d) more credits in basic math; and (e) fewer courses in midlevel and advanced math courses compared with their hearing peers (Nagle, Newman, Shaver, & Marschark, 2016). Finally, findings from the correlational study found students who were DHH attended regular secondary schools and had better spoken language and higher test scores (Marschark, Shaver, Nagle, & Newman, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Discussions surrounding academic outcomes for deaf students have long focused on the chronic gaps in reading, mathematics, and high school graduation rates between deaf individuals and their hearing peers (e.g., Garberoglio et al, 2019; Mitchell, 2017). In secondary settings, deaf students consistently underperform their hearing peers on standardized measures of academic achievement (Mitchell, 2017), take less rigorous coursework (Nagle et al, 2016), and complete high school at lower rates (Garberoglio et al, 2019). These achievement gaps are also visible in postsecondary settings: Deaf students enroll in developmental coursework to a significant extent (Garberoglio et al, 2019; Newman et al, 2011) and complete postsecondary degrees and certifications at lower rates than their hearing peers (Garberoglio et al, 2019).…”
Section: Systems Factorsmentioning
confidence: 99%